Analisis Tingkat Kesehatan Bank Dengan Menggunakan Pendekatan RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) (Studi pada PT. Bank Mandiri, Tbk Periode 2011-2013) - Pratiwi, Novanda Anggra; Nugraha, Adri Putra (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to determine the health of PT. Bank Mandiri Tbk in the period 2011-2013  that  was  measured  by using RGEC  approach  (Risk  Profile,  Good Corporate   Governance,   Earnings,   Capital).   This   research   is   quantitative descriptive research that using secondary data. The results of this study showed that the condition of PT. Bank Mandiri, Tbk is generally healthy, although there are some assessment aspects that are still in fairly good health level. Risk Profile on credit risk aspects, as measured by NPL ratio showed good condition, and market risk aspects as measured by IRR ratio also showed fairly good condition, and liquidity aspects as measured by LDR, LAR, and CR showed good condition. Good Corporate Governance consists of 11 assessment aspects that the total value of the composite are categorized as good. Earnings were measured by using ROA and NIM, this two ratios showed a high profitability level and are categorized in excellent condition. Capital were measured by CAR, the value of this ratio hang on excellent condition. The healthy condition reflects that the bank is able to manage  its  management  properly,  so  it  can  support  the  development  of  its business  and  can  anticipate the  changes  in  economic conditions  and  banking industry.   Keywords: bank health level, RGEC approach.